Does maggot therapy promote wound healing? The clinical and cellular evidence. (21st December 2015) - Nigam, Y.; Morgan, C.
Abstract: The larvae of Lucillia sericata, or maggots of the green‐bottle fly, are used worldwide to help debride chronic, necrotic and infected wounds. Whilst there is abundant clinical and scientific evidence to support the role of maggots for debriding and disinfecting wounds, not so much emphasis has been placed on their role in stimulating wound healing. However, there is accumulating evidence to suggest that maggots and their externalized secretions may also promote wound healing in stubborn, recalcitrant chronic ulcers. There are a growing number of clinical reports which support the observation that wounds which have been exposed to a course of maggot debridement therapy also show earlier healing and closure end‐points. In addition, recent pre‐clinical laboratory studies also indicate that maggot secretions can promote important cellular processes which explain this increased healing activity. Such processes include activation of fibroblast migration, angiogenesis (the formation of new blood vessels from pre‐existing vessels) within the wound bed, and an enhanced production of growth factors within the wound environment. Thus, in this review, we summarize the clinical evidence which links maggots and improved wound healing, and we précis recent scientific studies which examine and identify the role of maggots, particularly individual components of maggot secretions, on specific cellular aspects of wound healing.